Odpowiedź :
Odpowiedź:
a) 3(-2x+4) + 2(5a-3)=-6x+12+10a-6=
10a+6x+6
b)-3(3a-7x)+3(-2x+2)=-9a+21x-6x+6=9a+15x+9a
c)-2x(3a-5)+4a(3a-2x)=-6ax+10x+12a^2-8ax= -14ax+10x+12a^2
^ = do potęgi
d)-5a(x-4)-3x(-5x-3)= -5ax+20a+15x^2+9x
e) -4 (-2x+3) - 2x(-4a+1-x)=8x-12 +8ax -2x+2x^2=6x - 12 + 8ax+2x^2
a) (5x-3)(2a-3x)=10ax -15x^2-6a+9x
b) (-2a+4)(-3+5x)=6a+20x-12+20x6a - 12 +40x
c) (-5x+3)(-4+2x-a)=20x-10x^2+5a-12+6x-3a=26x-10x^2+2a
d)(3x-2)(-5a-4x^2)= -15ax-12x^2+10a+8x^2= -15ax-4x^2+10a
e) (-4a-3)(-5x+2)=20ax-8a+15x-6
f)3(x-2a)(5x-3)=3(5x^2-3x-10ax+6a)=15x^2-9x-30ax+18a